2022
DOI: 10.1021/acsomega.2c01008
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Proteomic Analysis in Male Mice Following Aggressive Behavior Induced by Long-Term Administration of Perampanel

Abstract: Antiepileptic drugs have been shown to be associated with inducing or exacerbating adverse psychotropic reaction, including aggressive behavior. Perampanel, the first pharmacological compound approved by the FDA in 2012, is an effective antiepileptic drug for intractable epilepsy but induces severe aggression. So far, the underlying molecular mechanisms of aggression induced by perampanel remain incompletely understood. In the present study, a model of aggressive behavior based on the clinical use of perampane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
(101 reference statements)
1
1
0
Order By: Relevance
“…Consistent with the above, several studies have shown that increased gene expression of the GluA1 subunit, as well as the relatively higher GluA1:GluA2 ratio [45] found in the present study, results in the synaptic insertion of a greater number of CP-AMPARs (Ca2 + ion-permeable AMPA receptors) [47], demonstrating a unique relationship between receptor expression, tra cking, and insertion in a variety of animal models of neurodegenerative disease [48].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the above, several studies have shown that increased gene expression of the GluA1 subunit, as well as the relatively higher GluA1:GluA2 ratio [45] found in the present study, results in the synaptic insertion of a greater number of CP-AMPARs (Ca2 + ion-permeable AMPA receptors) [47], demonstrating a unique relationship between receptor expression, tra cking, and insertion in a variety of animal models of neurodegenerative disease [48].…”
Section: Discussionsupporting
confidence: 90%
“…In addition to changes in the synthesis of the various proteins and structures that regulate the insertion and function of AMPA receptors, during the process of neuronal toxicity, neuroin ammation and neurodegeneration, the expression of the receptor subunits may be regulated by the administration of PER, as shown by Yang et al [45], who demonstrated that the chronic use of PER can positively regulate the GluA2 subunit. However, in the present study, PER decreased, although not signi cantly, the expression of the gene encoding GluA2 and especially GluA1 in the groups exposed to iron overload.…”
Section: Discussionmentioning
confidence: 99%